Free amino acid composition of apple juices with potential for cider making as determined by UPLC‐PDA. Issue 4 (4th October 2018) - Ma, Sihui; Neilson, Andrew P.; Lahne, Jacob; Peck, Gregory M.; O'Keefe, Sean F.; Stewart, Amanda C.
Abstract : Amino acids and ammonium ions constitute the yeast assimilable nitrogen naturally present in apple juice, with free amino acids being the major constituent. Little information is available on the extent to which free amino acid composition in apple ( Malus × domestica Borkh.) juice varies among juices used for fermentation. Twenty amino acids were quantified by UPLC‐PDA in juices from 13 apple cultivars grown in Virginia with potential use in cider making. The relative amino acid profile was significantly different among the apple juices evaluated. The total amino acid concentration ranged from 18 mg/L in Blacktwig juice to 57 mg/L in Enterprise juice.l ‐Asparagine, l ‐aspartic acid andl ‐glutamine are the principal amino acids observed in most apple juices. Our results indicate that the relative concentration of amino acids in apples is different from that found in Vitis vinifera wine grapes, which are rich inl ‐proline andl ‐arginine. The impact of these differences on fermentation of apple juice by wine yeast strains warrants further research, as the amino acid composition of grape juice impacts wine quality both directly and indirectly via yeast metabolism. These results will inform future research on yeast metabolism and nitrogen management during cider fermentation. © 2018 The Authors Journal of the Institute of Brewing published by John Wiley & Sons Ltd on behalf of The Institute of Brewing & Distilling